Physical literacy in older adults: a scoping review protocol - Galán-Arroyo, Carmen; de los Ríos-Calonge, Javier; Rojo-Ramos, Jorge; Parraca, Jose A.; Fonseca, Cesar; Castillo-Paredes, Antonio; da Silva Batista, Marco Alexandre (Frontiers in Public Health, 2024)
Population ageing is a prominent phenomenon worldwide. The increase in physical inactivity and comorbid diseases poses a major challenge to current community health policies. Physical activity guidelines recommended for older people have not been met by this population group. For this reason, a new model, physical literacy, is being innovated and has gained global attention and has emerged as an effective and innovative active ageing strategy to improve physical activity participation of this vulnerable group. However, the evidence on physical literacy in the elderly so far is brief and diffuse.